HAVE TEACHERS NEVER BEEN WRONG? CASE STUDIES OF MISCONCEPTIONS IN TEACHING MATHEMATICS IN ELEMENTARY SCHOOLS - Imam Kusmaryono; Nila Ubaidah; Nuhyal Ulya; Sri Kadarwati (Universitas Negeri Makassar, 2019)
Misconceptions of teaching mathematics in elementary schools often occur, not only to students but also experienced by teachers. Elementary school teachers are required to master many subjects where not all learning material (one of them mathematics) can be mastered by the teacher well. An elementary school teacher may be proficient in the field of language, but on the other hand is weak in the field of mathematics. So that it should be suspected, one of the causes of misconception in students is the teacher. Therefore, through a qualitative research approach, the types and causes of misconceptions in mathematics learning in elementary schools will be revealed by teachers. Research data was revealed through questionnaires and interviews. The findings show that there have been